High-Performance Planar Perovskite Optoelectronic Devices: A Morphological and Interfacial Control by Polar Solvent Treatment - Yu, Jae Choul; Kim, Da Bin; Baek, Gyoelim; Lee, Bo Ram; Jung, Eui Dae; Lee, Seungjin; Chu, Jae Hwan; Lee, Doh-Kwon; Choi, Kyoung Jin; Cho, Shinuk; Song, Myoung Hoon (WILEY-V C H VERLAG GMBH, 2015)
Highly efficient planar perovskite optoelectronic devices are realized by amine-based solvent treatment on compact TiO2 and by optimizing the morphology of the perovskite layers. Amine-based solvent treatment between the TiO2 and the perovskite layers enhances electron injection and extraction and reduces the recombination of photogenerated charges at the interface.
Keywords: POLYMER SOLAR-CELLS; ORGANOMETAL HALIDE PEROVSKITES; DOMINANT 001 FACETS; ORGANIC ELECTRONICS; LAYERED-PEROVSKITE; SURFACE SCIENCE; HOLE-CONDUCTOR; TIO2 SHEETS; EFFICIENT; ZNO